2021
DOI: 10.1002/ejoc.202101228
|View full text |Cite
|
Sign up to set email alerts
|

Zwitterionic Aromaticity on Azulene Extrapolated to carbo‐Azulene

Abstract: In memory of Klaus HafnerAzulene is stabilized by "zwitterionic aromaticity", what about its ring carbo-mer? The greater dipole moment of the latter is oriented in the opposite direction, while providing an enhanced zwitterionic aromatic character. Comparison of local aromaticity indices for the two rings, with 5 and 7 CÀ C bonds in azulene or CÀ C 2 À C edges in carbo-azulene, allows analysis of the quasiindependent influence of size on the π-electronic properties of these aromatic bicyclic molecules exhibiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 74 publications
(20 reference statements)
0
6
0
Order By: Relevance
“…The 10π-aromaticity of azulene was predicted in previous studies. , However, the relevance of this finding has been largely overlooked. For example, the permanent dipole moment of azulene is usually explained by resonance structures that invoke delocalization through the transannular bond, but these resonance structures do not significantly contribute to the net electronic structure of azulene (Figure a), as evidenced by the negligible Δ C 10 value. As a case in point, we found that homoazulene, the homoannelated counterpart of azulene without a conjugated transannular bond, has a similar permanent dipole moment (Chapter S13.1).…”
Section: Resultsmentioning
confidence: 99%
“…The 10π-aromaticity of azulene was predicted in previous studies. , However, the relevance of this finding has been largely overlooked. For example, the permanent dipole moment of azulene is usually explained by resonance structures that invoke delocalization through the transannular bond, but these resonance structures do not significantly contribute to the net electronic structure of azulene (Figure a), as evidenced by the negligible Δ C 10 value. As a case in point, we found that homoazulene, the homoannelated counterpart of azulene without a conjugated transannular bond, has a similar permanent dipole moment (Chapter S13.1).…”
Section: Resultsmentioning
confidence: 99%
“…For 2a , the 5MR moiety is concave, which indicates no magnetic shielding in the inner region of the 5MR moiety. In azulyne, the aromaticity can be justified by the presence of an ionic resonance structure that has a negative charge on the 5MR and a positive charge on the 7MR . In contrast, the ICSS zz magnetic shielding in 3a is similar to azulynes I – III , suggesting its aromaticity.…”
Section: Resultsmentioning
confidence: 99%
“…3 times less according to energetic criteria). 24 The rigid diameter of the π-system expands from 24.3 Å for 9 to 29.3 Å for 2 . While the frontier MOs of the parent molecule 9 spread over the antennas (HOMO over the thiophene rings, LUMO over the BTD units), those of the carbo -benzene 2 concentrate over the C 18 core (Table S3, ESI†).…”
Section: Resultsmentioning
confidence: 99%